2021
DOI: 10.1038/s41598-021-91595-4
|View full text |Cite
|
Sign up to set email alerts
|

Landscape condition influences energetics, reproduction, and stress biomarkers in grizzly bears

Abstract: Environmental change has been shown to influence mammalian distribution, habitat use, and behavior; however, few studies have investigated the impact on physiological function. This study aimed to determine the influence of landscape condition on the expression of target proteins related to energetics, reproduction, and stress in grizzly bears. We hypothesized that changes in landscape condition explains protein expression. Skin biopsies were collected from free-ranging grizzly bears in Alberta, Canada from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 102 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…Preliminary research has shown that measurable stress-induced heat shock protein Hsp70 in polar bears is positively correlated with fasting and negatively correlated with sea-ice extent (Hamilton, 2008), suggesting its use as an indicator of these food-related stressors. This is further supported by Wilson et al (2020bWilson et al ( , 2021, who identified and validated proteins from biopsied skin samples in grizzly bears and found that seasonality, year (as a proxy for environmental change), geography, conifer percentage (in complement C3 proteins), as well as a suite of biological attributes (i.e. age class, sex and age class × sex interaction) all have a strong and statistically significant influence on stress and other proteins.…”
Section: Emerging Methods For Measuring Stress In Bearsmentioning
confidence: 74%
“…Preliminary research has shown that measurable stress-induced heat shock protein Hsp70 in polar bears is positively correlated with fasting and negatively correlated with sea-ice extent (Hamilton, 2008), suggesting its use as an indicator of these food-related stressors. This is further supported by Wilson et al (2020bWilson et al ( , 2021, who identified and validated proteins from biopsied skin samples in grizzly bears and found that seasonality, year (as a proxy for environmental change), geography, conifer percentage (in complement C3 proteins), as well as a suite of biological attributes (i.e. age class, sex and age class × sex interaction) all have a strong and statistically significant influence on stress and other proteins.…”
Section: Emerging Methods For Measuring Stress In Bearsmentioning
confidence: 74%
“…Set points can be influenced, in part, by environmental factors that determine the somatic reserves necessary to meet long-term metabolic requirements within the context of the system within which an animal resides [ 16 ]. Nutritional indices may differ dramatically across populations—how animals catabolize and accrete resources to meet energetic and metabolic demands may indicate the synchronization of an animal’s physiology with its environment.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, biomarkers have been used as proxies to make inferences regarding physiological states and nutritional conditions [ 14 , 15 , 16 ]. Biomarkers can reveal the underlying drivers of behavior, fitness, and responses to environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, landscape features, movement, and disturbance together predict physiological state in grizzly bears (Wilson et al, 2021).…”
Section: Inflammatory and Immunementioning
confidence: 99%
“…For example, brown bears ( Ursus arctos) near human settlements have lower heart rate variability, a cardiovascular indicator of stress, and they move further during increased human activity, which is expected to have an energetic cost (Støen et al, 2015). Similarly, landscape features, movement, and disturbance together predict physiological state in grizzly bears (Wilson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%